Application of FAO/CIHEAM indices for dairy systems to dairy goat groups in western Andalusia - Sánchez M.; Gil M.J.; Fernández E.; Muñoz M.E. (Analyse technico-économique des systèmes de production ovine et caprine : méthodologie et valorisation pour le développement et la prospective., 2006)
With the aim of adapting the FAO/CIHEAM indices to the intensive system in western Andalusia, different flocks of dairy goats in the provinces of Cordoba and Seville hâve been studied. COVAP (Cooperativa del Valle de los Pedroches) data files and active inquiries to farmers (Murciano-Granadina breeders) have been used. Only one representative herd belonging to ACRIFLOR (Asociación Nacional de Criadores de Ganado Caprino de Raza Florida) has been included in the present study. All the studied farms are family-run and operate under intensive conditions even though they have a different number of goats. The technical and economic indices resulting from the study are positive, although greater cost-effectiveness is observed in larger flocks. The future of these farms is assured under the present conditions, that is, with similar milk prices and feeding costs, even without the support of European subsidies.
Séminaire du sous-réseau Systèmes de Production du réseau Interrégional FAO-CIHEAM de recherche et développement sur les ovins et caprins, 2005/06/16-18, Seville (Spain)